ЗНАЧЕНИЕ И МЕСТО ПРИРОДНОЙ РЕНТЫ В УСТОЙЧИВОМ РАЗВИТИИ КАЗАХСТАНА (Journal of Economic Research & Business Administration, 2015)
Improvement of the rent relationship takes up the principal position during the transit of the Republic of Kazakhstan to the sustainable development. First of all, there is a need for the science-based definition of the “sustainable development” conception which serves as theoretical base for the rent relationship. These issues are covered in the article.